Anisotropic torsional creep problems involving rapidly growing differential operators. (February 2020) - Stancu-Dumitru, Denisa
Abstract: The asymptotic behaviour of the sequence of positive solutions for a family of torsional creep-type problems involving anisotropic rapidly growing differential operators is studied in a bounded domain from the Euclidian space R N . We prove that the sequence of solutions converges uniformly on the domain to a certain distance function defined in accordance with the anisotropy of the problem.